Blood-Pressure and Cholesterol Lowering in Persons without Cardiovascular Disease - Yusuf, Salim; Lonn, Eva; Pais, Prem; Bosch, Jackie; López-Jaramillo, Patricio; Zhu, Jun; Xavier, Denis; Avezum, Alvaro; Leiter, Lawrence A; Piegas, Leopoldo S; Parkhomenko, Alexander; Keltai, Matyas; et al. (The New England journal of medicine, 2016)
In a 2-by-2 factorial trial, 12,705 persons at intermediate risk were assigned to candesartan plus hydrochlorothiazide or placebo and to rosuvastatin or placebo. At 5.6 years, combination therapy resulted in a significantly lower risk of cardiovascular events than dual placebo. Cardiovascular diseases are major causes of death and illness worldwide. 1 Both systolic blood pressure and low-density lipoprotein (LDL) cholesterol show graded associations with cardiovascular disease and together account for two thirds of the population-attributable risk of cardiovascular disease. 2 – 4 Therefore, combined lowering of LDL cholesterol and blood pressure can potentially have a bigger effect in reducing cardiovascular events than either intervention alone. Because the majority of cardiovascular events occur in persons at average risk with no previous cardiovascular disease, a strategy of broad population-based treatment of LDL cholesterol and blood pressure could be more effective than targeting only high-risk persons. . . .